From survey to analysis and visualization methods, new approaches to define rockfall hazard - Francioni, Mirko; Ferroni, Francesco; Ottaviani, Francesco; Ahmed, Mahnoor; Menichetti, Marco (Italian journal of engineering geology and environment, 2024)
Rockfalls are among the most dangerous natural hazards. The study of these phenomena may be complex in relation to the geology and the rock mass characteristics. Recent advances on the use of remote sensing techniques made the survey of rock slopes easier and faster, increasing the amount and quality of data. At the same time, the improved availability of software for characterizing rock slopes and simulating rockfalls permits a more detailed and precise definition of rockfall hazard areas. In this context, this research highlights the importance of using remote sensing techniques in the study of these phenomena, especially in developing accurate and reliable geological and structural models. The Regional Park of Monte Conero (Ancona, Italy) is used as the case example. The study area has been investigated through conventional geological/structural surveys, UAV photogrammetry and iPad-based LiDAR. The data gathered from surveys have been used to perform rockfall simulations and define potential mitigation measures. Finally, innovative visualization techniques based on the use of Virtual Reality will be introduced for an improved interpretation of geological and structural data and simulation results.